An Unconventional Method of Suicide by Corrosive Ingestion vis-à-vis Medicolegal Aspects – Autopsy based Brief Research - Kaushik, R; Jakhar, JK; Dahiya , S (Journal of Indian Academy of Forensic Medicine, 2024)
Defining the word suicide is just misconstruing the gravity, essence and biology behind the mood, thought and behaviour of developing it. Suicide is not an act but a complex behaviour. As per literal meaning, it is just killing of oneself by himself. The method of suicide chosen by the victim depends on their availability of method and intensity of impending impulse of suicide. The authors here are discussing various autopsy cases of fatal ingestion of corrosives. The autopsy findings over the body, proper history and pattern-distribution of injuries over the body are correlated to each other to know the cause and manner of death. The injuries sustained over the gastrointestinal tract due to corrosive ingestion are compared with the findings observed by the authors in different cases. The legal aspect of the acid related injuries are also discussed. This method of suicide by corrosive ingestion is quite rare. The clinical symptoms, investigative observation and treatment outcome varies widely with case to case depending upon the patient profile, tissue affected and concentration of corrosive. However, detailed history taking, psychological profile of patient and medical expert’s eye can diagnose the case on time which can save the patient with better prognosis.